The Frequency Of Posterior Segmental Pathologies Detected By B-scan Ultrasound In Preoperative Cataract Patients - Atiq, Taloot; Naeem, Ahmed; Ali, Abid; Jhon, Akash (Medical Science Journal for Advance Research, 2023)
Background: When we take dense cataract in consideration, the traditional ophthalmic techniques lacks the access to the posterior segment of the globe so the proper investigation of posterior segment becomes difficult. Ultrasonography is a useful tool for examining the posterior portion of the eye in patients who have cataract and for assessing structural changes in the posterior section of the eye Objective: To determine the frequency of posterior segmental pathologies detected by B-scan ultrasound in preoperative cataract patients Material and Methods: A cross sectional study conducted in Ibrahim Trust Eye Hospital. The data was collected using convenient sampling technique from February 2022 to May 2022 after written consent. A sample size of 165 was calculated using mean from previous published studies The patients of all ages were considered .The study included all the patients who had cataract. The equipment used for the evaluation was odm-2100 Ultrasonic A/B Scan Results: The age group that was most frequently reported were between 51 to 60 (34.5%).The minimum age of 31y and maximum age of 90y were reported .The female patients were more frequent as 91 (55.2%) and males as 74 (44.8%). 92 (55.8%) patients were reported positive for posterior segmental pathologies. The vitreous haemorrhage was most frequent pathology reported as in 50 patients (30.3%) The other pathologies that were reported include Retinal detachment (10.9%), Vitrits (6.7%), Vitreous opacities (4.2%), Posterior vitreous detachment (2.4%) and Choroidal detachment (1.2%) Conclusion: In conclusion, the current study shows that patients with cataract can have posterior segmental pathologies hidden behind lenticular opacification that is not visible with conventional ophthalmic diagnostic tools.